2011
DOI: 10.1007/s12519-011-0265-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotating shift work on childbearing and birth weight: a study of women working in a semiconductor manufacturing factory

Abstract: Rotating shift work exposure was significantly associated with decreased childbearing and lighter birth weight in women working in this semiconductor manufacturing factory. Work schedules should be carefully planned for female employees who are pregnant or preparing for pregnancy. Prenatal evaluations for mothers with persistent day-night rotating shift work exposures are especially necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
1
33
1
1
Order By: Relevance
“…It is well documented that shift work and sleep deprivation have significant effects on female hormonal status which in turn may be one of the reasons for such health effects. [1,6,7] The present study by Lin and co-workers clearly illustrates this. [1] The general stress of combining family life and household responsibilities with a full time job can also have negative impact on health and daily well being, particularly during pregnancy.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…It is well documented that shift work and sleep deprivation have significant effects on female hormonal status which in turn may be one of the reasons for such health effects. [1,6,7] The present study by Lin and co-workers clearly illustrates this. [1] The general stress of combining family life and household responsibilities with a full time job can also have negative impact on health and daily well being, particularly during pregnancy.…”
supporting
confidence: 80%
“…[8] One main paragraph deals with the woman's right to be transferred to lighter or less stressful jobs during pregnancy, such as being transferred from shift work and night work to continuous daytime work. As pointed out by Lin et al, [1] such replacement during pregnancy was also a possibility for their women. However, due to a substantial loss of salary when changing from shift work to continuous daytime work, this possibility was not considered by many of the women.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We decided to adjust for these confounders and additionally for other potential confounders that were a major risk factor (30% increased risk) for breast cancer and were found to be differentially associated with shift work. The final adjustment set therefore was: age (1,11,12), ethnicity (1,13,14), socioeconomic status (or a proxy) (10,(15)(16)(17), parity (16,(18)(19)(20)(21) with adjustment done for either number of children, or age at first child, and body mass index (BMI) (overweight, obese) (22)(23)(24).…”
Section: Confoundersmentioning
confidence: 99%
“…A study by Rao S et al to describe the relation of mother's physical activity to the birth size of her baby in rural Indian population, showed higher maternal activity in early as well as in mid gestation was associated with lower mean birth weight and a smaller neonatal head circumference 6 . Studies by Birnacka JB et al 7 , Naeye RL et al 8 , Rabkin CS et al 9 and Lin YC et al 10 found a lower birth weight in newborns born to working group of mothers. According to the present study, women need not worry about going to work during their pregnancy, but studies in larger numbers are required to know the clear picture.…”
Section: Discussionmentioning
confidence: 94%